Isolation of a mannose-binding and IgE- and IgM-reactive lectin from the seeds of Artocarpus integer - Lim, S.B.; Chua, C.T.; Hashim, Onn Haji (1997)
A mannose-binding lectin, termed champedak lectin-M, was isolated from an extract of the crude seeds of champedak (Artocarpus integer). On gel filtration chromatography, the lectin eluted in a single peak at elution volumes corresponding to 64 kDa, SDS-PAGE showed the mannose-binding lectin to be composed of 16.8 kDa polypeptides with some of the polypeptides being disulphide-linked to give dimers. When tested with all isotypes of immunoglobulins, champedak lectin-M demonstrated a selective strong interaction with human IgE and IgM, and a weak interaction with IgA2, The binding interactions of lectin-M were metal ion independent. The lectin was also shown to interact with horseradish peroxidase, ovalbumin, porcine thyroglobulin, human alpha(1)-acid glycoprotein, transferrin and alpha(1)-antitrypsin. It demonstrated a binding preference to Man alpha 1-3Man ligands in comparison to Man alpha 1-6Man or Man alpha 1-2Man. (C) 1997 Elsevier Science B.V.